DOPAMINE AGONIST-INDUCED IMPULSE CONTROL DISORDERS IN PATIENTS WITH PROLACTINOMA: A CROSS-SECTIONAL MULTI-CENTRE STUDY - Mak, Woh Wei; Bidin, Mohamed Badrulnizam Long; Noor, Nurain Mohd (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Dopamine agonists are the first-line agents in the treatment of symptomatic prolactinomas. One of the rare side effects of dopamine agonists is impulse control disorders (ICDs). The aim of this study is to determine the prevalence and associated risk factors of developing ICDs. METHODOLOGY This was a cross-sectional study involving 149 patients with prolactinoma in 2 tertiary centres who received at least a month of dopamine agonists. Demographics and blood results were retrieved from medical records. All patients underwent structured interview focused on ICDs using Barratt Impulsiveness Scale-11 (BIS-11) and Questionnaire for ImpulsiveCompulsive Disorders in Parkinson’s Disease (QUIP). BIS-11 score above 72 is used to classify an individual as impulsive. QUIP has 2 sections: Section 1 assesses four ICDs (gambling, sexual, buying, and eating), Section 2 assess other three other ICDs (punding, hobbyism, and walkabout). Patients were required to answer regarding whether they have behavioural changes at any time after the commencement of dopamine agonists. RESULT The mean age of the participants was 42, with a majority of them being female 117 (78.5%). The majority (n=93, 62.4%) were of Malay ethnicity. Ninety (61.1%) of the patients had microadenoma with baseline serum prolactin of 3251 uU/ml (IQR 500.6 uU/ml). Most of the participants 120 (80.5%) were on Cabergoline therapy, with median duration of treatment of 145 weeks and median current dose of 1mg weekly. The prevalence of ICDs was 39 (26.2%). The risk factor identified to be associated with ICD development was tertiary education level (Adjusted OR = 5.183, 95% CI [1.460, 18.402], p=0.011) after controlling for other confounding factors. CONCLUSION This study showed that ICDs are not uncommon with a prevalence of 26.2% among prolactinoma patients on dopamine agonists. Tertiary education level was identified as an associated risk factor. We recommend systematically screening for ICDs in all patients on dopamine agonists and providing forewarnings of possible ICD development among patients.